The Husk Charcoal Biobriquettes as Alternative Energy Based on Rice Husk Waste - Novisrayani Kesmayanti; Bahrul Ilmi (Future Science, 2022)
The decrease in the availability of gas and oil fuels has prompted government policy regulations that lead to the development and use of alternative energy. In Indonesia, there are many natural vegetable resources that can be used as alternative energy raw materials, one of which is rice husk waste. The Rice husk waste can be processed and utilized into bio-briquette husk charcoal which is environmentally friendly and has relatively high energy potential. This experiment aims to produce quality husk charcoal bio-briquettes with a neat and uniform shape, a solid structure, and not easy to break, as well as good combustion and composing power. Experimental treatments: The structure of husk charcoal (S) : S1 = mashed and S2 = not mashed. The composition of the adhesive dough (which is the ratio between tapioca flour and water) (A): A1 = 1 part tapioca: 5 parts water and A2 = 1 part tapioca: 7 parts water. The experimental results show that there are differences in physical characteristics between husk charcoal briquettes using mashed and unmashed husk charcoal as raw materials. The composition of the dough and the consistency of the adhesive also affect the quality of the husk charcoal briquettes. The combustion power and coals produced by briquettes from husk charcoal are better than those that are not mashed. The husk charcoal briquettes from a mixture of husk charcoal that were mashed with 1:5 dough composition and 1:7 had relatively the same characteristics. The combustion power of briquettes from the 1:5 dough composition is better than the 1:7 dough composition.